Anammox in treatment of coal chemical wastewater: a review - LI Lixin; LIU Sinan; KE Xiaojun; DONG Zilong; HUANG Linlin (矿业科学学报)
The coal chemical industry produces a large amount of difficult-to-degrade coking wastewater during its rapid development. Anaerobic ammonium oxidation (Anammox) demonstrates extensive application prospects in coal chemical wastewater treatment as it features low energy consumption, no addition of carbon sources, low sludge production and low greenhouse gas emissions. This study aims to explore the effect of Anammox in the treatment of coking wastewater, and proposes corresponding solutions to improve its treatment efficiency. The citation analysis software VOSviewer was used to conduct bibliometric analysis on the research progress of Anammox in the treatment of coking wastewater. We reviewed factors affecting the use of Anammox in the treatment of coking wastewater, We also expounded the advantages, mechanisms and economic benefits of Anammox. Then we summarized the difficulties in its application and put forward solutions to provide references for applying Anammox in coking wastewater treatment.